Pengaruh Motivasi Kerja, Disiplin Kerja dan Lingkungan Kerja Terhadap Kinerja Pengurus (Studi Kasus Tanaszaha Komisariat Malang Raya) - Vilda Afifah; Budi Wahono; Nanik Wahyuningtyas (E-JRM : Elektronik Jurnal Riset Manajemen, 2023)
Abstract This study aims to test the effect of work motivation, work discipline and work environment on the performance of the management at the Malang Raya Commissariat. This study uses the type of explanatory research with quantitative methods. The population in this study was a member of the Malang Raya Commissariat of Tanaszaha Organization. The sampling method in this study uses probability sampling with a type of proportionalate stratified random sampling technique, in this study the sample amounted to 54 respondents through the Google Form in accordance with the formula used, namely the Slovin formula. Data analysis in this study uses the assistance of SPSS 25.0 analysis aims to test the influence of work motivation, work discipline and work environment on the performance of the management. In this study results in work motivation positive and significant effect on the performance of the management, work disciplines have a positive and significant significant effect on the performance of the management, the work environment has a positive and significant effect on the performance of the management and for the influence of work motivation, work discipline and work environment The performance of the management of Tanaszahha Commissariat Malang Raya is 74.2% and the remaining 25.8% is influenced by other variables that are not in the study. Keywords: Work Motivation, Work Discipline, Work Environment, Management Performance